Evaluation of the hypocholesterolemic effect and prebiotic activity of a lentil (Lens culinaris Medik) extract. Issue 11 (29th August 2017) - Micioni Di Bonaventura, Maria Vittoria; Cecchini, Cinzia; Vila‐Donat, Pilar; Caprioli, Giovanni; Cifani, Carlo; Coman, Maria Magdalena; Cresci, Alberto; Fiorini, Dennis; Ricciutelli, Massimo; Silvi, Stefania; Vittori, Sauro; Sagratini, Gianni
Abstract : Scope: The aim of our work was to produce a hydroalcoholic extract of lentils and to examine (a) the hypocholesterolemic action in an animal model, by studying the plasma cholesterol level and the concentration of bile acids in the feces; (b) the potential prebiotic effect, by conducting an in vitro culture fermentation experiment and assessing the level of SCFAs in the feces of rats. Methods and results: Lentil extract (LE) was obtained by extracting lentils with a solution of H2 0/EtOH (70/30 v/v) for 3 h, and the content of main nutrients was determined. After 71 days of diet‐induced hypercholesterolemia in rats, LE reduced the cholesterol level of rats of 16.8% ( p < 0.05) and increased the level of bile acids in the feces of rats ( p < 0.01). LE revealed the same prebiotic activity of inulin and good bifidogenic activity, inasmuch as it enhanced the growth of Bifidobacterium spp. by 3 log ( p < 0.05). The concentration of SCFAs in the feces of rats fed with LE increased during the time of the study. Conclusion: This new hydroalcoholic extract obtained from lentils was shown to possess hypocholesterolemic and prebiotic properties, and could have interesting applications in the field of nutraceuticals. Abstract : Lentils are a source of bioactive compounds such as soyasaponins that are responsible of hypocholesterolemic and prebiotic activity. In this study, a new hydroalcoholic extract obtained from lentils was shown to possess hypocholesterolemic and prebiotic properties, and could have interesting applications in the field of nutraceuticals.